Are Asian fresh and brackish water aquaculture production vulnerable or resilient towards climate change impacts?. Issue 3 (2nd July 2020) - Nadarajah, Suthamathy; Eide, Arne
Abstract: This study analyzes fresh and brackish water aquacultures—especially carp, tilapia, and shrimp production—in major Asian aquaculture-producing countries. Different indicators have been used, involving dimensions that may be affected by climate change. High diversity is believed to indicate high adaption capacity, while resilience is estimated by known biological properties of each species. The results confirm that China, by far, has the largest diversity of species and values, followed by Bangladesh, Indonesia and Vietnam. Evaluation of the resilience of major species in light of the impacts climate change may have on warming, seawater intrusion and reduced fish meal supply, indicates that shrimp species are more resilient than tilapia, carp and catfish. In general, resilience of aquaculture products in Asia seems to be high, and the aquaculture production could adapt to climate change impacts by proper modifications in farming systems and infrastructure facilities in the future.